COMMUNIST CAROTIC ARTERY CLOSURE DURATION EFFECT ON WISTAR WHITE RATS MOTORIC - Daswara Djajasasmita; Hindun Sa'adah; Miftahudin (Fakultas Kedokteran Gigi Unjani, 2021)
The carotid artery consists of two carotid arteries, namely the dextra communist artery and the sinistra, the main blood vessels in the neck that supply blood to the brain, the basal ganglia, which have the function of regulating the motor functions of the body. The communal carotid arteries blocked flow can cause brain ischemia. It is due to hypoxia due to a lack of oxygen supply carried by the brain, resulting in motor body function disorders, incredible blockages in the carotid arteries that supply blood to the brain, and neurons as regulators of motor functions. The research is a literature study that has relevance to the formulation of the problem meets the criteria and research objectives to determine the effect of the length of the blockage of the arteries of the carotid artery of the communist to the motor function of the Wistar strain rats. The results of a literature review or literature studies in some previous scientific research journals indicate if the blockage of the arteries of the communal carotid arteries affects the disruption of motor function caused by hypoxia and damage to neurons and brain tissue in motor neurons. The conclusion is that the blockage and the duration of blockage of the communal carotid arteries affect motor function. DOI : 10.54052/jhds.v1n2.p153-164